2007
DOI: 10.1590/s0100-204x2007001200005
|View full text |Cite
|
Sign up to set email alerts
|

Análise multidimensional de consórcios cenoura-alface sob diferentes combinações de densidades populacionais

Abstract: Este trabalho teve como objetivo avaliar o desempenho biológico de sistemas consorciados de cenoura e alface, sob diferentes combinações de densidades populacionais, com uso das análises bivariada de variância e envoltória de dados (DEA). O delineamento experimental usado foi o de blocos ao acaso completos, com cinco repetições, com os tratamentos arranjados em esquema fatorial 4x4. Os tratamentos resultaram da combinação de quatro populações de plantas de cenoura (40, 60, 80 e 100% da população recomendada no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…However, significant effects of the main factors were observed. With the increase in population densities of carrot and lettuce from 40 to 100% of the recommended population in mono-cropping system, we found an increase of 24 and 12.5% respectively, in production capacity (Bezerra Neto et al, 2007).…”
Section: Introductionmentioning
confidence: 69%
“…However, significant effects of the main factors were observed. With the increase in population densities of carrot and lettuce from 40 to 100% of the recommended population in mono-cropping system, we found an increase of 24 and 12.5% respectively, in production capacity (Bezerra Neto et al, 2007).…”
Section: Introductionmentioning
confidence: 69%
“…Bezerra Neto et al (2007a), Bezerra Neto et al (2007b and Bezerra Neto et al (2007c) observed, respectively, effectiveness and ease in the utilization of the DEA method, as well as robustness of the bivariate analysis of variance; viability of the multicriteria decision support method and of the utilization of agro-economic indicators for biological productivity of intercropping systems. The recommended methods, except that of bivariate analysis, are object of study of the functional relation between resources and products in production engineering.…”
Section: Introductionmentioning
confidence: 96%
“…In general, the methods are non-parametric and multivariate. This is due to the multivariate nature of the data resulting from the joint evaluation of agronomic and economic parameters (BEZERRA NETO et al, 2007a). Contrasting with the parametric methods presented by Federer (1993), the statistical analyses at plot level with data envelopment analysis (DEA) was suggested by Bezerra Neto et al (2007a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O sistema de cultivo consorciado é bastante difundido entre os produtores rurais de regiões tropicais, cujos fatores climáticos, como temperatura e radiação solar não apresentam limitações. Bezerra Neto et al (2007) explicam que esta técnica consiste no plantio de mais de uma cultura, simultaneamente, numa mesma área de terra, durante parte ou todo o período de desenvolvimento das culturas.…”
Section: Introductionunclassified